Attitudes and readiness of nurses towards digitalisation - Calvin Mabaso; Ramasela Mokonyama; Jeremy Mitonga-Monga (Curationis)
Background: This study examines nurses’ attitudes and readiness to integrate digital technologies, particularly electronic medical records (EMR), in a South African private hospital group. Understanding these perspectives is vital as healthcare increasingly digitises.